Application of rumen-protected lysine to lower crude protein diets for lactating dairy cows - Pretz, Jon Patrick (Kansas State University, 2013)
The study objective was to evaluate the application of supplemental rumen-protected lysine (RP Lys) to maintain milk production when reducing the crude protein levels in a lactating dairy cow diet. Twelve lactating multiparous Holstein cows, averaging 129 DIM, 50.2 kg milk yield, 3.6% fat and 2.9% true protein were randomly assigned to one of four 3x3 Latin squares. Each 14-d period had 11 d for adaptation followed by 3 d of data collection. Cows were offered one of three experimental treatment rations formulated with CPM Dairy (v3.0); Positive control (PC) — formulated to meet all nutrient requirements; Test diet (Test) — negative control diet formulated to meet nutrient requirements, except deficient in metabolizable protein (MP) (approximately 200 g/d) and first limiting in metabolizable Lys (approximately 10 g/d); and Test+RPL — same basal diet as negative control + RP-Lys to provide 14.5 g/d of MP-Lys. For Test+RPL, 45g of RP-Lys (AminoShure-L®; Balchem Corp., New Hampton, NY, containing 23.4g Lys) was top-dressed on the TMR once daily. The PC diet resulted in lower dry matter intake (P = 0.03) as compared to either the Test or Test+RPL diet. PC, Test, and Test+RPL cows averaged 42.6, 42.9, 43.6 kg/d of milk and 27.3, 28.4, 28.8 kg/d of DMI, respectively. Crude protein intake for the PC, Test, and Test+RPL diets was 4.83, 4.67, and 4.74 kg/d respectively. MUN decreased (P < 0.01) for cows on Test and Test+RPL diets as compared to PC diet (12.5, 12.5 and 14.9 mg/dL, respectively). Milk yield, milk components, milk component yields, FCM, ECM, SCM and production efficiencies (milk, ECM, SCM and FCM) did not differ (P > 0.05) among treatments. A post-study CPM Dairy evaluation using final chemical composition analyses of the feedstuffs and average production data from the animals predicted that diets supported more than 47 kg of milk and Lys was not limiting. Cows on the study produced slightly less milk, however DMI was 5-8% more than predicted by initial formulations. Formulation accuracy of the MP and Lys deficient diet may have been improved if data had been available from an initial adjustment period measuring DMI, body weight, milk yield and milk composition. It is also possible that the bioavailability of the RP Lys was not as great as thought during the diet formulation process. However, given the fact that the post-trial CPM analysis did not indicate a deficiency of Lys, it is not very likely that this impacted the results of this trial.
Keywords: Amino acids; Crude protein; Dairy cattle; Agriculture, General (0473); Animal Sciences (0475); Nutrition (0570)